PENERAPAN MEDIA KANTONG BILANGAN UNTUK MENINGKATAN HASIL BELAJAR MATEMATIKA SISWA KELAS 1 DI SDN 1 JENGGIK - Rabiatun Adwiah; Nurhikmah Nurhikmah (LP2M Universitas Adzkia, 2025)
This study aims to improve mathematics learning outcomes using number bag media for first-grade students of SDN 1 Jenggik. This study is a Classroom Action Research (CAR), which includes planning, implementation, observation, and reflection in each cycle. Data analysis uses quantitative and qualitative data analysis. Based on the results of the research that has been conducted, the use of number bag media can improve student learning outcomes. This can be seen from the number of students as many as 15 students who completed 9 students (60%) and those who have not completed 6 students (40%), increasing in cycle II to 13 students (86.67%) who completed and those who have not completed 2 students (13.33%). This proves that the use of number bag media can improve the mathematics learning outcomes of first-grade students at SDN 1 Jenggik